FIRST-PRINCIPLES STUDY OF PLATINUM SINGLE-ATOM CATALYST SUPPORTED BY GRAPHENE NANORIBBONS - Arman Wella, Sasfan
The single-atom catalysis has been expected to be one of the most promising ways not only for reducing the amount of precious metals used, but also for enhancing the catalytic activity. Platinum atoms deposited on graphene has been reported to show enhanced catalytic activity for some chemical reactions, e.g. methanol oxidation in direct methanol fuel cells. Nonetheless, the precise atomic structure, the key to understand the origin of the improved catalytic activity, has yet to be clarified. By means of first-principles calculations based on density functional theory, interactions between single Pt atoms and graphene, with special emphasis on the edges of graphene, are investigated to clarify the origin of improved catalytic reactivities. Thermodinamically, it is found that the single Pt atom preferentially adsorbs at the edge rather than on graphene, a good news regarding the search of a dense single atoms dispersion on a support material. In addition, the calculated core level shift (CLS) for the stable structures are in reasonable agreement with the experiment, corroborating our findings. The large positive CLS indicates the strong interaction between single Pt atoms and graphene. Furthermore, the catalytic activity of single Pt atoms anchored at the edges of graphene nanoribbons is also predicted based on the atomic and molecular adsorption energies from DFT calculations combined with some kinetic models. Compared with the Pt(111) surface, the single Pt atoms supported by graphene edges show a better activity in CO oxidation reaction, which is presumably the origin for the improved CO tolerance in the anode electrode in direct methanol fuel cell. Some single Pt atoms in metastable configurations are also suggested could be efficient catalysts for oxygen reduction reaction. This study could be a basis for further investigation of the development of single-atom catalysts based on platinum and graphene related materials.